A case series of sinonasal mucormycosis and actinomycosis infection: a clinicopathological approach - Arushi Gupta; Shaan Khetrapal; Safia Rana; Zeeba Shamim Jairajpuri; Sabina Khan; Sujata Jetley; Seema Monga (MGM Journal of Medical Sciences)
Background: Mucormycosis is a fast-progressing and life-threatening fungal infection caused by fungi belonging to the order Mucorales. It primarily affects individuals with weakened immune systems or diabetes mellitus (DM). Case Reports: This study includes eight patients aged from 24 to 68 years (six males and two females), all of whom presented to the ear, nose, and throat department with primary complaints of nasal obstruction. Histopathological evaluation of biopsies confirmed mucormycosis, revealing areas of necrosis. After appropriate treatment, all patients showed improvement. Discussion: Histopathological examination is the gold standard for diagnosing fungal infections like mucormycosis and actinomycosis. Hematoxylin and eosin staining typically shows necrotic tissue, a mix of acute and chronic inflammatory cells, and broad, nonseptate fungal hyphae. Conclusion: Mucormycosis is the third most common angioinvasive fungal infection and carries a high mortality rate. Successful management requires early diagnosis, aggressive surgical intervention, and timely antifungal therapy. Additionally, controlling underlying conditions, such as DM, is critical in both preventing and treating this serious infection. This case series underscores the importance of thorough histopathological evaluation and heightened clinical awareness when diagnosing and managing sinonasal infections in immunocompromised patients.